Domestic resource mobilisation strategies of national non-governmental development organisations in Ghana - Emmanuel Kumi (University of Bath, Centre for Development Studies (CDS), 2017)
National non-governmental development organisations (NNGDOs) in Ghana are confronted with declining external donor funding, arising in part from the country's promotion to a lower-middleincome status, but also more complex changes in external funding modalities. This presents incentives for mobilisation of alternative domestic resources to ensure organisational survival. Drawing on 62 qualitative interviews with NNGDOs leaders, donor representatives and key informants, this article presents findings on how NNGDOs in Ghana are responding to this challenge. In particular, the article focuses on resource diversification. NNGDOs mobilised five main domestic resources: a) corporate philanthropy; b) individual donations and diaspora remittances; c) volunteer support; d) earned income through commercialisation and e) government funding. We conclude that while reduced external donor funding is an immediate threat to civil society space in Ghana, social innovations in domestic resources in response to it offer limited potentials for NNGDOs financial sustainability.
Keywords: 330; Funding modalities; domestic resource mobilisation; NGDOs; Ghana